1975
DOI: 10.1136/hrt.37.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Malignant hypertension associated with use of oral contraceptives.

Abstract: A 26-year-old woman who had been taking an oral contraceptive preparation for two years Zacherle and Richardson (I972) described a case in which severe hypertension developed while the patient was on oral contraceptives. Antihypertensive agents controlled the blood pressure satisfactorily and the blood pressure remained normal after withdrawal of all therapy. Reintroduction of a sequential oral contraceptive agent 3 years later again resulted in severe hypertension associated on this occasion with early hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies have repeatedly reported increases in blood pressure with current hormonal contraception use [ 4 , 6 , 13 - 15 ]. These studies also demonstrated that this effect quickly diminishes once hormonal contraception is stopped [ 6 , 13 , 15 , 16 ]. Very few studies have focused on past hormonal contraception use and risk of subsequent high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have repeatedly reported increases in blood pressure with current hormonal contraception use [ 4 , 6 , 13 - 15 ]. These studies also demonstrated that this effect quickly diminishes once hormonal contraception is stopped [ 6 , 13 , 15 , 16 ]. Very few studies have focused on past hormonal contraception use and risk of subsequent high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in colonic salt and water transport can have important implications for total body water and electrolyte balance. There is a dramatic increase in plasma oestrogen concentrations during gestation (Preedy & Aitken, 1961; Roy & Mackay, 1962) – and in other high oestrogen states such as certain phases of the menstrual cycle (Thorn & Engel, 1938), and during use of the combined oral contraceptive pill – and this has been associated with salt and water retention resulting in oedema and hypertension (Katz & Kappas, 1967; Dunn et al ., 1975; Laragh, 1976; Fisch & Frank, 1977). Previous studies from our laboratory have demonstrated a down‐regulation of net chloride secretion and an up‐regulation of sodium reabsorption following addition of 17β‐oestradiol in human distal colon (McNamara et al ., 1995; 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Dunn et al presented a case of a young lady with a history of hypertension and being overweight who developed MH after taking oral contraceptive preparations for two years. Control of her BP was obtained by the withdrawal of the oral contraceptive agent and antihypertensive therapy [ 8 ]. Weir et al found the increase in systolic blood pressure to be the same in women taking either low-dose or high-dose estrogen oral contraceptive preparations [ 4 ].…”
Section: Discussionmentioning
confidence: 99%